2018
DOI: 10.1002/chem.201705707
|View full text |Cite
|
Sign up to set email alerts
|

Cp2TiX Complexes for Sustainable Catalysis in Single‐Electron Steps

Abstract: We present a combined electrochemical, kinetic, and synthetic study with a novel and easily accessible class of titanocene catalysts for catalysis in single-electron steps. The tailoring of the electronic properties of our Cp TiX-catalysts that are prepared in situ from readily available Cp TiX is achieved by varying the anionic ligand X. Of the complexes investigated, Cp TiOMs proved to be either equal or substantially superior to the best catalysts developed earlier. The kinetic and thermodynamic properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 85 publications
1
32
0
Order By: Relevance
“…Experimental studies on the use of electron deficient catalysts have demonstrated that they lead to substantially lower rate constants (e.g. Cp 2 TiOMs: k 293 =0.013 M −1 s −1 ) compared to Cp 2 TiCl (k 293 =1.1 M −1 s −1 ) [10d] . The HAT step is strongly exergonic in line with the difference in stability of tertiary and benzylic radicals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental studies on the use of electron deficient catalysts have demonstrated that they lead to substantially lower rate constants (e.g. Cp 2 TiOMs: k 293 =0.013 M −1 s −1 ) compared to Cp 2 TiCl (k 293 =1.1 M −1 s −1 ) [10d] . The HAT step is strongly exergonic in line with the difference in stability of tertiary and benzylic radicals.…”
Section: Resultsmentioning
confidence: 99%
“…We employed Cp 2 Ti(O 3 SCH 3 ) 2 that is a stronger oxidant than Cp 2 TiCl 2 due to the more electron withdrawing mesylate ligand [10d] . In this manner, additional driving force for the reductive elimination is provided.…”
Section: Resultsmentioning
confidence: 99%
“…As described for conventional chromophores [91] and metal complexes, [92] both optical and electrochemical properties of titanocenes can be reasonably controlled, making those complexes even more attractive catalysts for the development of new radical-triggered transformations in which the photoredox properties of a chromophores match those of titanocenes. [93][94][95] Based on these grounds, one might identify suitable chromophores with given excited state properties (i.e. energy, deactivation kinetics and redox potentials) able to perform oxidative PET to reduce Cp 2 Ti IV Cl 2 ( Figure 3B).…”
Section: Titanocenes: Photophysics and Electrochemistrymentioning
confidence: 99%
“…As described for conventional chromophores [ 91 ] and metal complexes, [ 92 ] both optical and electrochemical properties of titanocenes can be reasonably controlled, making those complexes even more attractive catalysts for the development of new radical‐triggered transformations in which the photoredox properties of a chromophores match those of titanocenes. [ 93–95 ]…”
Section: Titanocenes: Photophysics and Electrochemistrymentioning
confidence: 99%
“…However, it was also found that the titanium catalysts were rather quickly deactivated and the corresponding zirconium compounds showed much higher stability and catalytic activity. Thus, the mainstream research on metallocene catalysts stopped for titanium-based metallocenes nearly completely until recently when the concepts of "Green Chemistry" and "Sustainable Catalysis" came into play [9][10][11][12]. Another area of "applied research" opened up after the discovery that Cp 2 TiCl 2 showed antitumor activity [13][14][15].…”
Section: Introductionmentioning
confidence: 99%